THE EFFECT OF USING DURIAN (Durio zibethinus) SEED FLOUR ON CHARACTERISTICS OF CATFISH (Pangasius hypophthalmus) NUGGETS - Sahrul Ramadhan; Mirna Ilza; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThe study aimed to determine the effect of using different durian (Durio zibethinus) seed flour on the characteristics of catfish (Pangasius hypophthalmus) nuggets. The research was carried out with an experimental method, which was the experiment of making catfish nugget using different amounts of durian seed flour. The treatments used were without durian seed flour (N0), 33.33% of durian seed flour (N1), 66.66% of durian seed flour (N2), and 100%  of durian seed flour (N3). The design used was a non-factorial Completely Randomized Design with 3 repetitions. The results showed that the using 100% of durian seed flour was the best treatment to produce the highest characteristics of catfish nuggets. The characteristics of the catfish nugget contained  water, protein, crude fiber, fat, and ash content were  3.03%, 59.99%, 7.67%, 4.42%, 13.72%, and 3.03%, respectively.Keywords: nuggets, catfish, characteristics